2019
DOI: 10.1021/acs.chemmater.9b00362
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, Electronic Structure, and Vibrational Properties of Snn(S1–xSex)m Solid Solutions for Energy Applications

Abstract: The tin sulfides and selenides have a range of applications spanning photovoltaics and thermoelectrics to photocatalysts and photodetectors. However, significant challenges remain to widespread use, including electrical and chemical incompatibilities between SnS and device contact materials and the environmental toxicity of selenium. Solid solutions of isostructural sulfide and selenide phases could provide scope for optimizing physical properties against sustainability requirements, but this has not been comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 79 publications
1
39
0
Order By: Relevance
“…We recently carried out a study of four Sn n (S 1-x Se x ) m alloys [26], including the Pnma and rocksalt monosulphides, by performing first-principles calculations on the full sets of symmetry-inequivalent structures formed by substituting chalcogen atoms in small supercells of the parent structures [28]. In this study we also confirmed the stability of the mixed Pnma Sn(S 1-x Se x ) alloys and further predicted the effect of alloying on the structural, electrical and optical properties [26].While many large-scale modelling studies make use of (semi-)local DFT methods to evaluate and compare energetics and electrical properties [29][30][31][32], modelling lattice dynamics and in particular thermal transport can be much more resource intensive, and there are thus comparatively fewer examples of screening studies focussing on these properties [33]. As a result, despite the widespread use of alloying to tune the performance of thermoelectric materials, there has been little theoretical investigation into how composition affects the dynamics and related properties.…”
supporting
confidence: 71%
See 4 more Smart Citations
“…We recently carried out a study of four Sn n (S 1-x Se x ) m alloys [26], including the Pnma and rocksalt monosulphides, by performing first-principles calculations on the full sets of symmetry-inequivalent structures formed by substituting chalcogen atoms in small supercells of the parent structures [28]. In this study we also confirmed the stability of the mixed Pnma Sn(S 1-x Se x ) alloys and further predicted the effect of alloying on the structural, electrical and optical properties [26].While many large-scale modelling studies make use of (semi-)local DFT methods to evaluate and compare energetics and electrical properties [29][30][31][32], modelling lattice dynamics and in particular thermal transport can be much more resource intensive, and there are thus comparatively fewer examples of screening studies focussing on these properties [33]. As a result, despite the widespread use of alloying to tune the performance of thermoelectric materials, there has been little theoretical investigation into how composition affects the dynamics and related properties.…”
supporting
confidence: 71%
“…However, the substantial difference in the mixing energy may be important in systems with competing phases. In our previous work [26,42], we predicted based on lattice energies that the energy difference between competing Pnma and rocksalt Sn(S 1-x Se x ) monochalcogenide solid solutions varies from 10.5 and 2.6 kJ mol −1 per F.U. between the SnS and SnSe endpoints [26].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations